COST Action TU1406: main outcomes from the first training school - Matos, José C. (2017)
During the implementation of asset management strategies, maintenance actions are required in order to retain assets at a desired performance level. In case of roadway bridges, specific performance indicators are established for their components. These indicators can be qualitative or quantitative based, and they can be obtained during principal inspections, through visual examination, non-destructive testing or temporary or permanent monitoring system. Then, obtained indicators are compared with performance goals, in order to evaluate if the quality control plan is accomplished. It is verified that there is a large disparity in Europe regarding the way these indicators are quantified and how such goals are specified. Therefore, COST Action TU1406 aims to bring together, for the first time, both research and practicing communities in order to accelerate the establishment of a European guideline in this subject.